Childhood maternal care is associated with DNA methylation of the genes for brain-derived neurotrophic factor (BDNF) and oxytocin receptor (OXTR) in peripheral blood cells in adult men and women. (4th July 2015) - Unternaehrer, Eva; Meyer, Andrea Hans; Burkhardt, Susan C. A.; Dempster, Emma; Staehli, Simon; Theill, Nathan; Lieb, Roselind; Meinlschmidt, Gunther
Abstract: In adults, reporting low and high maternal care in childhood, we compared DNA methylation in two stress-associated genes (two target sequences in the oxytocin receptor gene, OXTR ; one in the brain-derived neurotrophic factor gene, BDNF ) in peripheral whole blood, in a cross-sectional study (University of Basel, Switzerland) during 2007–2008. We recruited 89 participants scoring < 27 ( n = 47, 36 women) or > 33 ( n = 42, 35 women) on the maternal care subscale of the Parental Bonding Instrument (PBI) at a previous assessment of a larger group ( N = 709, range PBI maternal care = 0–36, age range = 19–66 years; median 24 years). 85 participants gave blood for DNA methylation analyses (Sequenom R EpiTYPER, San Diego, CA) and cell count (Sysmex PocH-100i™, Kobe, Japan). Mixed model statistical analysis showed greater DNA methylation in the low versus high maternal care group, in the BDNF target sequence [Likelihood-Ratio (1) = 4.47; p = 0.035] and in one OXTR target sequence Likelihood-Ratio (1) = 4.33; p = 0.037], but not the second OXTR target sequence [Likelihood-Ratio (1) < 0.001; p = 0.995). Mediation analyses indicated that differential blood cell count did not explain associations between low maternal care and BDNF (estimate = −0.005, 95% CI = −0.025 to 0.015; p = 0.626) or OXTR DNA methylation (estimate = −0.015, 95% CI = −0.038 to 0.008; p = 0.192). Hence, low maternal care in childhood was associated with greater DNA methylation in an OXTR and a BDNF target sequence in blood cells in adulthood. Although the study has limitations (cross-sectional, a wide age range, only three target sequences in two genes studied, small effects, uncertain relevance of changes in blood cells to gene methylation in brain), the findings may indicate components of the epiphenotype from early life stress.